Vienna on the path to modernism = Uin modan kurimuto shire seikimatsu eno michi - Bunzl, Matti 1971- (The Yomiuri Shimbun, 2019)
Art movements flourished in the late 19th to early 20th century in Vienna as artists sought new forms of expression that stepped beyond traditional media definitions of painting, sculpture, decorative arts, design and fashion. Through their efforts they began what would become the highly decorative, glittering splendor of a uniquely Viennese cultural form. Major artists emerged in all genres during this fin de siècle period, including painters such as Gustav Klimt (1862-1918), Egon Schiele (1890-1918), and Oskar Kokoschka (1886-1980), the architect Otto Wagner (1841-1918), Josef Hoffmann (1870-1956), Adolf Loos (1870-1933), and the designer Koloman Moser (1868-1918), heralding a golden age of modern art and design. This flourishing occurred not only in the visual arts, it can also be found in music, psychology and other fields.--Gallery website
Frontispizseite: "Vienna on the Path to Modernism. The 150th Anniversary of the Establishment of Diplomatic Relation between Japan and Austria", Tokyo, April 24 - August 5, 2019, The National Art Center, Tokyo; Osaka, August 27 - December 8, 2019, The National Museum of Art, Osaka
Keywords: Geschichte 1750-1930; Design; Kunst; Architektur; Wien; Ausstellungskatalog -- Kokuritsu Shinbijutsukan -- 24.04.2019-05.08.2019 -- Tokio; Ausstellungskatalog -- Kokuritsu-Kokusai-Bijutsukan -- 27.08.2019-08.12.2019 -- Osaka